Autoimmunity and tuberculosis. Opposite association with TNF polymorphism (2005)
Objective. To examine the influence of the –308 and –238 single nucleotide polymorphisms (SNP) of tumor necrosis factor-? gene (TNF) on patients with systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), primary Sjögren’s syndrome (SS), and tuberculosis (TB). Methods. Genomic DNA from patients with RA (n = 165), SLE (n = 100), primary SS (n = 67), and TB (n = 135) and ethnically matched controls (n = 430) was genotyped for TNF –308 and –238 SNP by PCR-RFLP. Results. TNF –308A allele was associated with RA (odds ratio, OR 1.8, p = 0.002), SLE (OR 2.6, p < 0.0001), and primary SS (OR 2.9, p < 0.0001). TNF –308G was associated with TB (OR 1.8, p = 0.02). The –308 GG genotype was protective for autoimmunity (p < 0.003). TNF –238A allele was protective for autoimmunity but represented a susceptibility factor for TB (OR 2.2, p < 0.0001). Haplotype –308A–238G was a protective factor against TB, whereas it carried susceptibility for RA, SLE, and primary SS (p < 0.0001). Conclusion. The results show an opposite association of TNF polymorphism with autoimmunity and TB, and suggest the existence of heterozygote advantage, sustaining the hypothesis that autoimmune diseases are a consequence of natural selection for enhanced TB resistance. Data also provide genetic evidence supporting the common variants/multiple disease hypothesis, which emphasizes that many disease genes may not be disease-specific, and that similar immunogenetic mechanisms underlie autoimmune diseases. (J Rheumatol 2005;32:219–24)